Thermodynamic study on the integrated supercritical water gasification with reforming process for hydrogen production: Effects of operating parameters. (13th September 2018) - Hantoko, Dwi; Su, Hongcai; Yan, Mi; Kanchanatip, Ekkachai; Susanto, Herri; Wang, Guobin; Zhang, Sicheng; Xu, Zhang
Abstract: In this paper, a conceptual process design of the integrated supercritical water gasification (SCWG) and reforming process for enhancing H2 production has been developed. The influence of several operating parameters including SCWG temperature, SCWG pressure, reforming temperature, reforming pressure and feed concentration on the syngas composition and process efficiency was investigated. In addition, the thermodynamic equilibrium calculations have been carried out based on Gibbs free energy minimization by using Aspen Plus. The results showed that the higher H2 production could be obtained at higher SCWG temperature, the H2 concentration increased from 5.40% at 400 °C to 38.95% at 600 °C. The lower feed concentration was found to be favorable for achieving hydrogen-rich gas. However, pressure of SCWG had insignificant effect on the syngas composition. The addition of reformer to the SCWG system enhanced H2 yield by converting high methane content in the syngas into H2 . The modified SCWG enhanced the productivity of syngas to 151.12 kg/100kgfeed compared to 120.61 kg/100kgfeed of the conventional SCWG system. Furthermore, H2 yield and system efficiency increased significantly from 1.81 kg/100kgfeed and 9.18% to 8.91 kg/100kgfeed, and 45.09%, respectively, after the modification. Graphical abstract: Image 1 Highlights: A process design by integrating of SCWG and reforming process was proposed. Utilizing reformer to enhance the H2 productivity was developed. The potential sewage sludge as energy resources has been considered. The effect of operating condition on the process performance was examined. Feed concentration and temperature had a significant effect on the process performances.